Interdisciplinary management of an impacted dilacerated maxillary central incisor - Harpreet Singh; Pranav Kapoor; Poonam Sharma; Pooja Dudeja; Raj Kumar Maurya; Surbhi Thakkar (Dental Press Journal of Orthodontics)
ABSTRACT Introduction: Tooth dilacerations are dental anomalies characterized by an abrupt deviation in the longitudinal axis of a tooth. They may occur either in the crown, between the crown and root, or in the root. Although not so common, impacted maxillary incisors exhibiting root dilaceration pose a diagnostic and treatment challenge to the clinician. Description: This case report describes the management of a horizontally impacted and dilacerated maxillary central incisor in a 12-year-old girl. Cone-beam computed tomographic scans were used to accurately localize the position of the dilacerated tooth, and to assess the extent of root formation and degree of dilaceration present in the root. Treatment included surgical exposure and orthodontic traction, followed by root canal treatment and apicoectomy. Results: Through a meticulously planned interdisciplinary approach, the impacted dilacerated central incisor was properly aligned and demonstrated good stability after the long-term follow-up. Conclusion: Taking into consideration the concerns and expectations of the patient, communicative feedback between the oral surgeon, orthodontist and endodontist helped achieving successful esthetic, structural and functional outcome in the present case.